Gaya Kepemimpinan Kepala Madrasah dalam Meningkatkan Etika Manajemen di MAN 1 Kota Jambi - Wardatul Jannah; Mahmud MY; Riftiyanti Savitri (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2020)
This study aims to describe the leadership style of madrasah heads in improving management ethics in MAN 1 Jambi City. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results found that in improving management ethics in madrasah, the principal adhered to a democratic leadership style. The application of democratic leadership to establish management ethics goes well, resulting in positive values such as values of service orientation, integrity, commitment, discipline, cooperation and all actions based on ethical criteria, namely in terms of benefits, the fulfillment of rights, the justice side, and the maintenance side. There are three values of management ethics obtained, namely personal value as an ethical standard, terminal value (purpose); and instrumental value.